The Influence of Shift Work Compensation and Job Satisfaction on Employee Work Productivity at SPBU in Palopo City - Raja, Arya Wira; Ntopu, Aan; Pawindu, Feni; Sukirman, Putri; Erwina, Erwina; Amri, Amri (Universitas Syiah Kuala, 2025)
This study aims to determine and analyze the influence of shift work compensation and job satisfaction on work productivity at two gas stations in Palopo City, namely SPBU PT Josila Trimakmur and SPBU Dangerakko. The background of this research is based on the importance of human resources, particularly in the public service sector such as gas stations. This research is a quantitative study. The types of data used include both primary and secondary data. Data collection methods include observation, interviews, and questionnaires. The sample consisted of 30 employees. The data were analyzed using descriptive analysis, validity tests, reliability tests, and multiple linear regression analysis. The results of the study indicate that, partially, shift compensation and work shifts do not have a significant effect on work productivity, while job satisfaction has a significant effect. Simultaneously, all three variables have a significant effect on employee work productivity.